THE ROLE OF THE EXTERNAL AUDITOR IN MONITORING THE COMPLIANCE OF GULF COMMERCIAL AND BAGHDAD BANKS WITH THE INSTRUCTIONS OF THE CENTRAL BANK OF IRAQ REGARDING CAPITAL ADEQUACY RATIOS (CASE STUDY OF GULF COMMERCIAL AND BAGHDAD BANKS) - Lec. Ali Miri Hassan; Lec.Oday Jasim Challab (Scholar Express Journals, 2024)
The study aims to show the role of the external auditor in monitoring the compliance of Gulf Commercial Bank and Baghdad Bank with the instructions of the Central Bank of Iraq regarding capital adequacy ratios, as the study sought to show this in the study of the two banks, as the ratio that maintains the capital adequacy ratio is not less than (10%) before the formation of the prudential pillar and not less than (12.5%) after the formation of the prudential pillar. The analytical method was used to draw the results, as it was reached through our examination of the accounting records of Baghdad Bank and our review of the nature of the banking operations practiced by the bank during the year under audit. The statements prepared for the purpose of calculating capital adequacy, where the capital adequacy ratio as of the budget date (52%) and the Gulf Commercial Bank (34%) of the capital and sound reserves, given that the ratio specified by the Central Bank (12.5%). This indicates the bank's compliance with the instructions of the Central Bank of Iraq regarding capital adequacy ratios. The study recommended that commercial banks operating in the Iraqi banking sector should continue to adhere to the regulatory controls related to the capital adequacy standard, during which the banks submit their data in accordance with the applicable controls on the capital adequacy standard along with the new controls in parallel to ensure the integrity of the systems and to ensure the validity of the data.
Keywords: External Auditor; Central Bank of Iraq Controls; Capital Adequacy